Apakah Al-Qur’an Memerlukan Hermeneutik - Suharto, Ugi (Jurnal Usuluddin, 2003)
This paper questions the need to adopt "hermeneutics" as a method in Qur’anic exegesis. It argues that "hermeneutics" might be useful in biblical studies, since Bible has a textual problem known to the Jews and the Christians. However, according to Muslims, such a problem is not there in the case the Qur’an. Therefore, they do not need hermeneutics. Muslims, believing that the Qur’an is the Words of God, only need tafsir and ta’wil to understand the messege of the Qur’an. Applying "hermeneutics" in the Qur’anic commentary would imply that there is, like in other Holy Scriptures, a textual problem in the Qur’an. This, consequently, would induce Muslims to think that their Holy Book is also suffering from the lack of authenticity.